2018
DOI: 10.1002/jbm4.10078
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cortical Porosity and Reduced Trabecular Density Are Not Necessarily Synonymous With Bone Loss and Microstructural Deterioration

Abstract: Absolute values of cortical porosity and trabecular density are used to estimate fracture risk, but these values are the net result of their growth‐related assembly and age‐related deterioration. Because bone loss affects both cortical and trabecular bone, we hypothesized that a surrogate measure of bone fragility should capture the age‐related deterioration of both traits, and should do so independently of their peak values. Accordingly, we developed a structural fragility score (SFS), which quantifies the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…A thinner cortex and increased cortical porosity at the proximal femur were associated with increased risk of fractures . The importance of coexisting cortical and trabecular deterioration for fracture propensity has recently been demonstrated using CT at distal forearm in women . Lower femoral neck BMD, lower TBS, and more prevalent vertebral fractures on VFA express lower total bone strength, which in this study is associated with serious fractures like hip and vertebral fractures, fractures that previously have been shown to be associated with increased morbidity and mortality …”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…A thinner cortex and increased cortical porosity at the proximal femur were associated with increased risk of fractures . The importance of coexisting cortical and trabecular deterioration for fracture propensity has recently been demonstrated using CT at distal forearm in women . Lower femoral neck BMD, lower TBS, and more prevalent vertebral fractures on VFA express lower total bone strength, which in this study is associated with serious fractures like hip and vertebral fractures, fractures that previously have been shown to be associated with increased morbidity and mortality …”
Section: Discussionsupporting
confidence: 52%
“…(23) The importance of coexisting cortical and trabecular deterioration for fracture propensity has recently been demonstrated using CT at distal forearm in women. (24,25) Lower femoral neck BMD, lower TBS, and more prevalent vertebral fractures on VFA express lower total bone strength, which in this study is associated with serious fractures like hip and vertebral fractures, fractures that previously have been shown to be associated with increased morbidity and mortality. (26)(27)(28)(29) Prospective studies have shown that low BMD measured at central, (17) as well as peripheral sites, (30,31) predicts any type of fracture.…”
Section: Discussionmentioning
confidence: 60%
“…Cross‐sectional studies demonstrate that a measurement of microstructural deterioration distinguishes women with osteopenia and prevalent fractures from women with osteopenia without fractures . Recent prospective studies support the notion that microstructural deterioration identifies women with osteopenia having incident fractures …”
Section: Introductionmentioning
confidence: 94%
“…In this edition of the JBMR , Chapurlat and colleagues present a study in which they have investigated the association between incidence of fracture and a structural fragility score (SFS) derived from HRpQCT distal forearm measurements . The SFS score was developed by relating cortical porosity and trabecular density of the distal radius in postmenopausal women with radius fracture to reference values for these parameters in premenopausal women without fractures . HRpQCT assessments provide much more detail, including microstructural and geometric properties, than DXA does.…”
mentioning
confidence: 99%
“…For example, measuring BMD at the hip provides the most accurate estimate for hip fracture prediction, indicating that site specificity is an important factor to consider. In the study by Chapurlat and colleagues, the SFS score used was originally derived from a cross‐sectional cohort of women with and without radius fracture . The SFS score then proved to be superior to DXA BMD of the femoral neck and FRAX in predicting fractures in two French cohorts of postmenopausal women (OFELY and QUALYOR) with mean ages of included women from 66 to 68 years.…”
mentioning
confidence: 99%